A Qualitative Exploration of Self-Management Behaviors and Influencing Factors in Patients With Type 2 Diabetes - Peng, Xi; Guo, Xinhong; Li, Hongmei; Wang, Dan; Liu, Chenxi; Du, Yaling (Frontiers in Endocrinology, 2022)
Background and Aims: The self-management behavior of patients with diabetes involves a complex set of actions involving medication therapy, lifestyle changes, and management of complications in the daily routine. Our study aims to explore adherence to self-management behaviors by patients with type 2 diabetes and the potential factors influencing those behaviors. Methods: This qualitative study used semi-structured interviews conducted with patients who have type 2 diabetes and who were recruited from the department of endocrinology in a tertiary teaching hospital. Data were analyzed thematically using the interview framework. Results: Overall, 28 patients with type 2 diabetes were recruited and interviewed. Three types of medication noncompliance behaviors were coded. In particular, blindly optimistic attitudes toward the condition in younger patients who had a short duration of diabetes and fear of or pain from medication therapy were key influencing factors. Irregular monitoring and missed follow-up visits were the most frequently mentioned noncompliance behaviors. Poor understanding of blood glucose monitoring, selective ignorance due to pressure of uncontrolled blood glucose, and blindly optimistic attitudes were also identified as key influencing factors. Dietary behaviors were characterized by an overemphasis on the amount of food in the diet and the preference or declination for particular types of food; ignorance of the dietary structure was present. Misconceptions about dietary and exercise practices were the main types of lifestyles’ noncompliance. Conclusion: Our study showed the complex picture of noncompliance with self-management behaviors by patients with type 2 diabetes. Noncompliance covered disordered and arbitrary changes in medication therapy, blood glucose monitoring with poorest adherence, lifestyle modifications and complication management. The study findings identify clear challenges to self-management behavior and identify potential key influencing factors. Future interventions and strategies should aim to help patients translate healthcare provider’s information and instructions into action that improve compliance.